The contribution of the nurse manager to healthy labour relations - Part 1 - Marthie Bezuidenhout (AOSIS, 1998)
With the persisting unrest in health services, the relevance and importance of labour relations as a component of management cannot be over emphasised. Opsomming Met die voortdurende onrus in gesondheidsdienste, kan die relevansie en belang van arbeidsverhoudinge as 'n komponent van bestuur nie oorbeklemtoon word nie. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.